2022
DOI: 10.3390/diagnostics12102392
|View full text |Cite
|
Sign up to set email alerts
|

An Explainable Machine Learning Pipeline for Stroke Prediction on Imbalanced Data

Abstract: Stroke is an acute neurological dysfunction attributed to a focal injury of the central nervous system due to reduced blood flow to the brain. Nowadays, stroke is a global threat associated with premature death and huge economic consequences. Hence, there is an urgency to model the effect of several risk factors on stroke occurrence, and artificial intelligence (AI) seems to be the appropriate tool. In the present study, we aimed to (i) develop reliable machine learning (ML) prediction models for stroke diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Given the age-related nature of the disease, since more than half of all patients are aged over 65 [ 3 ], in combination with the increasing global population and the constant improvement of life expectancy [ 4 ], the number of stroke survivors will rise in an unprecedented manner. Consequently, the early and precise recognition of patients with unfavorable prognoses is essential in order to personalize treatment and tailor rehabilitation to each individual’s needs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the age-related nature of the disease, since more than half of all patients are aged over 65 [ 3 ], in combination with the increasing global population and the constant improvement of life expectancy [ 4 ], the number of stroke survivors will rise in an unprecedented manner. Consequently, the early and precise recognition of patients with unfavorable prognoses is essential in order to personalize treatment and tailor rehabilitation to each individual’s needs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…From Table 2, it is observed that the proposed Rough-Fuzzy based Synthetic Data Generation (RFSDG) method provides the best result when the RF classifier model is applied to BS (obtained using both oversampling and undersampling technique) dataset. So, we have considered RFSDG + RF as the final proposed model and compared it with some state-of-the-art methods Chawla et al [11], Lee and Kim [59], Schölkopf et al [60], Vuttipittayamongkol and Elyan [61], Zhenchuan Li [20], Kokkotis et al [62], described below.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…Thus, a crucial need for prompt and accurate identification of patients with an unfavorable prognosis has emerged. Additionally, such an approach may allow the development of personalized rehabilitation programs based on the propensity for recovery of each individual [ 4 ].…”
Section: Introductionmentioning
confidence: 99%